2016
DOI: 10.1007/s11912-016-0508-y
|View full text |Cite
|
Sign up to set email alerts
|

Brachytherapy in Gynecologic Cancers: Why Is It Underused?

Abstract: Despite its established efficacy, brachytherapy is underused in the management of cervical and vaginal cancers in some parts of the world. Possible reasons for the underutilization of brachytherapy include the adoption of less invasive techniques, such as intensity-modulated radiotherapy; reimbursement policies favoring these techniques over brachytherapy; poor physician or patient access to brachytherapy; inadequate maintenance of brachytherapy skills among practicing radiation oncologists; transitioning to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Multiple studies have reported suboptimal use of cervical BT, including access to facilities, increased overall treatment time, and sometimes omission of BT in favor of less effective external RT techniques. 27-29 A need for a call to international action involving multiple stakeholders was therefore recently discussed at the World Cancer Congress, 30 and a joint international initiative is being envisaged to map international access to cervical cancer EBRT and BT. It is also predicted that the joint initiative would work toward a financial investment plan and estimate the impact of inaction, with an aim of improving international infrastructure for treatment of LACC in the next decade.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have reported suboptimal use of cervical BT, including access to facilities, increased overall treatment time, and sometimes omission of BT in favor of less effective external RT techniques. 27-29 A need for a call to international action involving multiple stakeholders was therefore recently discussed at the World Cancer Congress, 30 and a joint international initiative is being envisaged to map international access to cervical cancer EBRT and BT. It is also predicted that the joint initiative would work toward a financial investment plan and estimate the impact of inaction, with an aim of improving international infrastructure for treatment of LACC in the next decade.…”
Section: Discussionmentioning
confidence: 99%
“…With three dimensional treatment planning using CT, or better, MRI, brachytherapy is even more effective and safe (53). Yet brachytherapy usage is declining (54). The reasons for underutilization of brachytherapy include insufficient training of residents in radiation oncology with isolation from gynecologic oncologists, intensive requirement for physics support, poor access to BT, and relatively inadequate reimbursement rates compared to other radiation modalities.…”
Section: Radiation Therapy Deliverymentioning
confidence: 99%
“…The use of brachytherapy declined significantly in recent years. [3,18] In this case, further investigation is required to evaluate the effect of radiotherapy in cervical cancer, to better understand the disparity of response to radiotherapy among patients with different demographic and pathological characteristics.…”
Section: Discussionmentioning
confidence: 99%